Theoretical and experimental analysis of heat transfer in the layers of road pavement = Analiza teoretyczna i badania doświadczalne wymiany ciepła w warstwach jezdni drogowej - Aliawdin, Piotr; Marcinowski, Jakub; Wilk, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A heat transfer problem for the road pavement system "layered plate - embankment - soil base" is formulated. There are suggested mathematical models in this work; they are realized with finite element analysis and design software COSMOS/M by solving layer plate on the ground foundation. Transient thermal state for this road structure is defined in numerical analysis by discretization of the system "layered plate ? embankment ? soil base" with triangular finite elements described by different material properties. The numerical results are compared with the experiment data for the real road pavement of Lubuski province road No 297 on the route Zagan-Kozuchow in Poland.
Keywords: nawierzchnia drogowa; droga wojewódzka; wymiana ciepła; model matematyczny; road pavement system; embankment; heat transfer problem; mathematical models; experimental and numerical results